2006
DOI: 10.1248/cpb.54.1318
|View full text |Cite
|
Sign up to set email alerts
|

Major Metabolites of Zolpidem: Expeditious Synthesis and Mass Spectra

Abstract: An expeditious route to the two major metabolites of Zolpidem-and readily applicable to the synthesis of the drug-was established via a cyclization reaction between a 2-aminopyridine and a suitable a a-bromoacetophenone. The structures of the target compounds were confirmed from a 2D 1 H-15 N NMR correlation. Their mass spectra contribute to a reliable toxicological identification of the drug in the case of drug-facilitated crimes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 13 publications
2
3
0
1
Order By: Relevance
“…For mono‐oxygenated‐zolpidem isomers M1 and M2, the loss of CH 2 O from the pseudo‐molecular ions to produce a fragment at m / z 294.1603 indicated that each of these metabolites contained a hydroxyl group on one of the two primary carbon substituents of the aromatic rings. Furthermore, the MS/MS spectrum of carboxyzolpidem (M5) contained product ions at m / z 221.1074, 265.0974, and 293.0923, which is consistent with the previously reported11 MS/MS spectrum of N , N ,6‐Trimethyl‐2‐(4‐carboxyphenyl)‐imidazo[1,2‐ a ]pyridine‐3‐acetamide (zolpidem with a methyl group on the phenyl ring replaced by a carboxy function). These authors also previously reported the MS/MS spectrum of N , N ,dimethyl‐6‐carboxy‐2‐(4‐methylphenyl)‐imidazo[1,2‐ a ]pyridine‐3‐acetamide (zolpidem with a methyl group on the imidazo[1,2‐ a ]pyridine ring replaced by a carboxy function).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…For mono‐oxygenated‐zolpidem isomers M1 and M2, the loss of CH 2 O from the pseudo‐molecular ions to produce a fragment at m / z 294.1603 indicated that each of these metabolites contained a hydroxyl group on one of the two primary carbon substituents of the aromatic rings. Furthermore, the MS/MS spectrum of carboxyzolpidem (M5) contained product ions at m / z 221.1074, 265.0974, and 293.0923, which is consistent with the previously reported11 MS/MS spectrum of N , N ,6‐Trimethyl‐2‐(4‐carboxyphenyl)‐imidazo[1,2‐ a ]pyridine‐3‐acetamide (zolpidem with a methyl group on the phenyl ring replaced by a carboxy function). These authors also previously reported the MS/MS spectrum of N , N ,dimethyl‐6‐carboxy‐2‐(4‐methylphenyl)‐imidazo[1,2‐ a ]pyridine‐3‐acetamide (zolpidem with a methyl group on the imidazo[1,2‐ a ]pyridine ring replaced by a carboxy function).…”
Section: Resultssupporting
confidence: 91%
“…These authors also previously reported the MS/MS spectrum of N , N ,dimethyl‐6‐carboxy‐2‐(4‐methylphenyl)‐imidazo[1,2‐ a ]pyridine‐3‐acetamide (zolpidem with a methyl group on the imidazo[1,2‐ a ]pyridine ring replaced by a carboxy function). In contrast to the former carboxyzolpidem isomer, this second previously reported isomer lacked a product ion at m / z 221 and instead produced a fragment at m / z 219 11. Taken together from the results of the current study, the presence of m / z 221.1075 in the spectrum of mono‐oxygenated‐zolpidem isomer M1 and its absence from that of M2, indicate that the positions of hydroxylation in these two isomers are on the primary methyl groups attached to the phenyl and imidazo[1,2‐ a ]pyridine rings respectively.…”
Section: Resultsmentioning
confidence: 59%
“…6f) elutes after the parent drug which would be in line with its postulated N-oxide structure. Finally, the mass shifts of +30 mass units in both side chain fragments in comparison to the parent can be assigned to the tolyl carboxy metabolite which has also been described in the literature [30,31].…”
Section: Identification Of Metabolitesmentioning
confidence: 73%
“…6e). Both of these metabolic reactions have been described in the literature [30,31]. A further hydroxy metabolite carrying the hydroxyl function at the tolyl moiety has also been described in the literature [30].…”
Section: Identification Of Metabolitesmentioning
confidence: 92%
“…Pour établir les fenêtres de détection du zolpidem et de ses métabolites dans les urines, les métabolites I et II ont été synthétisés [11], puis une méthode d'extraction en phase solide (SPE) et de détection par UPLC-MS/MS a été développée.…”
Section: Introductionunclassified